2018
DOI: 10.1002/chem.201705822
|View full text |Cite
|
Sign up to set email alerts
|

Structural Factors Affecting Binding of Platinum Anticancer Agents with Phospholipids: Influence of Charge and Phosphate Clamp Formation

Abstract: We report a detailed NMR and DFT study of the interaction of polynuclear platinum anticancer agents (PPCs) with negatively charged phospholipids as a mechanism for their cellular uptake. The reactions of fully N-labelled [{trans-PtCl(NH ) } (μ-trans-Pt(NH ) {NH (CH ) NH } )] ( N-1, 1,0,1/t,t,t) and the dinuclear [{trans-PtCl(NH ) } {μ-H N(CH ) NH }] ( N-2, 1,1/t,t) with the sodium salt of 1,2-dihexanoyl-sn-glycero-3-phosphate (DHPA) were studied at 298 K, pH ≈5.4, by [ H, N] HSQC 2D NMR spectroscopy. Both N-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…For both adducts, coordination of the DHPA molecule by the phosphate O atom places the cis-NH 3 in a similar hydrogen bonded environment to that previously reported for the Pt-NH 3 groups in 1,1/t,t, 10 and this peak (δ 3.86/−65.3, labelled C m ) is similarly deshielded in both 1 H (∆δ = 0.10) and 15 N (∆δ = 0.7) dimensions with respect to the parent chlorido species. The Pt−NH 2 group (δ 4.56/−43.5), which is similarly cis to the coordinated DHPA molecule, exhibits a similar deshielding with respect to the parent chlorido complex ( 1 H ∆δ = 0.07, 15 N ∆δ = 0.7).…”
Section: Nmr Studiessupporting
confidence: 76%
See 3 more Smart Citations
“…For both adducts, coordination of the DHPA molecule by the phosphate O atom places the cis-NH 3 in a similar hydrogen bonded environment to that previously reported for the Pt-NH 3 groups in 1,1/t,t, 10 and this peak (δ 3.86/−65.3, labelled C m ) is similarly deshielded in both 1 H (∆δ = 0.10) and 15 N (∆δ = 0.7) dimensions with respect to the parent chlorido species. The Pt−NH 2 group (δ 4.56/−43.5), which is similarly cis to the coordinated DHPA molecule, exhibits a similar deshielding with respect to the parent chlorido complex ( 1 H ∆δ = 0.07, 15 N ∆δ = 0.7).…”
Section: Nmr Studiessupporting
confidence: 76%
“…The Pt−NH 2 group (δ 4.56/−43.5), which is similarly cis to the coordinated DHPA molecule, exhibits a similar deshielding with respect to the parent chlorido complex ( 1 H ∆δ = 0.07, 15 N ∆δ = 0.7). The trans-NH 3 group (δ 4.21/−83.6) is noticeably shielded in the 1 H dimension (∆δ −0.08) with respect to the parent chlorido complex, whereas in the case of 1,1/t,t the 1 H shifts for the analogous Pt-NH 2 protons were almost identical in species A and C. 10 By observing the change in intensity of trans-NH 3 peak for the unbound {PtN 3 Cl} group (C m' Fig. 1) the mono-DHPA adduct (1,1/c,c-MF-1) reached a maximum intensity after about 9 h, and then decreased so that it represents only 2% of the total Pt species at equilibrium Bifunctional adduct formation.…”
Section: Nmr Studiesmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, recent studies have reported the interactions of such negatively charged phospholipids with polynuclear platinum anticancer agents to facilitate cellular uptake. 100 The synthesis of hexadecylphosphono-(L)-serine 333 was reported by Brachwitz et al The transesterication reaction was carried out by stirring a mixture of hexadecyl phosphonocholine 332 and excess (L)-serine, at a ratio of 1 : 100, with phospholipase D, which is known to convert phosphatidylcholine into phosphatidylserine (Scheme 77). 101 Aer treatment, the crude substance was puried via chromatography on cellulose to furnish the phosphonoserine 333 with 28% yield.…”
Section: The Phosphorylation and Phosphination Of Hydroxyamino Acids mentioning
confidence: 99%